THE RELATION BETWEEN STUDENT’S PERCEPTION OF LEARNING ENVIRONMENT AND LEARNING MOTIVATION OF PRE-CLINICAL MEDICAL STUDENT - Zafira Pringgoutami; Rika Lisiswanti; Dwita Oktaria (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: Academic achievement is influenced by two factors, internal and external factor. Learning environment is one of the external factors that affect the academic achievement. A conducive learning environment can improve students learning motivation and affect academic achievement.The aim of this research is to find out the relation between student’s perception of learning environment and learning motivation of pre-clinical student in Medical Faculty of Lampung University.Methods: This research was using cross sectional approach. The sample of this research consisted 248 pre-clinical student in Medical Faculty of Lampung University which determined by proportional-random sampling. This research used two questionnaires: Dundee Ready Educational Environment Measure (DREEM) and Motivated Strategies of Learning Questionnaire (MSLQ). Data were analysed using Spearman.Results: The result showed that most of pre-clinical student in Medical Faculty of Lampung University have perception about learning environment was decent (74,6%) and learning motivation was high (98,8%), there was significant relation between student’s perception of learning environment and learning motivation which determined by p value <0,05 and r 0,462.Conclusion: From this research can be concluded that the better student’s perceptions of learning environment, the higher learning motivation becomes.